2014
DOI: 10.1155/2014/646128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of End-to-Side Neurorrhaphy: An Update

Abstract: End-to-side neurorrhaphy constitutes an interesting option to regain nerve function after damage in selected cases, in which conventional techniques are not feasible. In the last twenty years, many experimental and clinical studies have been conducted in order to understand the biological mechanisms and to test the effectiveness of this technique, with contrasting results. In this updated review, we consider the state of the art about end-to-side coaptation, focusing on all the current clinical applications, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
1
26
0
1
Order By: Relevance
“…The regulation of matrix metalloproteinase (MMP) expression and activity [20] as well as neurotrophic factors (TIMPs and IGF) [12,40] might also have very important roles in this process. Recent experimental studies have shown that physical and chemical agents stimulate nerve regeneration after end-toside coaptation, including phototherapy, FK506, and acetyl-L-carnitine [13,24,32,57].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of matrix metalloproteinase (MMP) expression and activity [20] as well as neurotrophic factors (TIMPs and IGF) [12,40] might also have very important roles in this process. Recent experimental studies have shown that physical and chemical agents stimulate nerve regeneration after end-toside coaptation, including phototherapy, FK506, and acetyl-L-carnitine [13,24,32,57].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory axons will spontaneously sprout from the healthy into the injured nerve, providing a kind of protective sensation, although it is never fully normal [11,65,66]. Meanwhile, donor nerve motor axons need an injury (crush or axotomy) to sprout inside an end-to-side coapted damaged nerve [66,69]. It can be useful for sensory nerves but not for motor ones.…”
Section: End-to-end Anastomosismentioning
confidence: 99%
“…[ [26][27][28][29][30] The authors of the current study intend to study the usefulness of this procedure in the scenario of acute trauma of the upper limb by creating nerve bridges at the wrist crease in order to ameliorate ulnar nerve injury, as it has been found that intrinsic muscle function tends to be compromised despite the efforts of a primary end-to-end repair.…”
Section: ]mentioning
confidence: 99%